Association of multilocus sequence typing, MSH2 gene mutations, and antifungal resistance in Candida glabrata: implications for clinical outcomes in Chinese hospitals - Guanyi Zhang; Yisheng Chen; Jia Chen; Dongting Yao (BMC, 2024)
Abstract Background Candida glabrata is the second most common cause of invasive candidiasis worldwide. In this study, we determined the clinical characteristics and drug sensitivity of C. glabrata isolates and investigated the associations between MSH2 gene mutations, sequence types (ST), and drug resistance. Methods A total of 154 C. glabrata isolates were collected from patients being treated in three hospitals in China. The antifungal sensitivity of the strains was assessed using the broth microdilution method. Multilocus sequence typing (MLST) was also performed, followed by MSH2 sequencing. The clinical features and outcomes of C. glabrata infection were analysed for a total of 49 strains, which were collected from patients with invasive Candida infection at Longhua Hospital. Results All 154 isolates were found to be susceptible to amphotericin, 5-fluorocytosine, anidulafungin, caspofungin, and micafungin, whereas 11.7% were fluconazole-resistant, 18.8% were itraconazole non-wild type, and 35.7% were voriconazole non-wild type. ST7 (62.34%) was the most common ST genotype, followed by ST10 (16.88%) and ST15 (7.79%). The total azole resistance rates for all isolates, ST7, ST10, and other STs were 36.4, 42.7, 34.6, and 18.8%, respectively. The ST7 and ST10 isolates were characterised by a higher drug resistance rate than the other minor ST isolates. Moreover, 59.09% of isolates had one or more MSH2 non-synonymous mutations, with V239L being the most commonly detected mutation. The frequency of MSH2 mutations was significantly higher in azole-resistant isolates than in other isolates, whereas P6L or L87P mutations were associated with the highest azole resistance rates of up to 87.5% and 80%, respectively. Our results indicated that ST7 and ST15 are independent predictors of mortality caused by C. glabrata infection and revealed a higher 30-day mortality in patients infected with these strains than in those infected with other ST isolates. Conclusions Our findings revealed the relationships between MLST, MSH2 gene mutations, and drug resistance in the common pathogenic fungus C. glabrata, and thereby enabled us to identify strains that are associated with higher rates of mortality. These findings will contribute to enhancing our understanding of the pathogenesis of C. glabrata infection.